The Impact of the Internet on Retail Competition: Evidence from Technological Differences in Internet Access - Georg Gebhardt (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2010)
Does the internet increase competition? To address this question, I exploit two institutional details unique to Germany: (1) Some municipalities received glass fibre cables that cannot be upgraded to DSL; I use these municipalities as a treatment group with reduced online competition. (2) German law mandates resale price maintenance for books; I compare three retailing sectors, electronics (price competition), books (no price competition), and food (no online sales), to identify the effect of price competition: The effect of price competition is highly significant. Full broadband access reduces offline electronics retailers' producer rents by 1.5 percent per year from 1999 to 2007.
urn:nbn:de:bvb:19-epub-13209-4
Keywords: D43; L81; L13; 330; Internet; Market Structure; Retail Competition; Differences in Differences; Internet; Online-Handel; Marktstruktur; Einzelhandel; Preiswettbewerb; Breitbandkommunikation; Schätzung; Deutschland